Effect of stress and temperature on the thermomechanical degradation of a PE-LD/OMMT nanocomposites - Mantia, F. P. La; Morreale, M.; Ceraulo, M.; Mistretta, M. C. (Polimery, 2014)
Thermomechanical degradation of nanocomposites is a topical issue that has not been fully investigated as demonstrated by the low number of papers available in the literature regarding this specific aspect. In particular, with regards to low density polyethylene/clay nanocomposites, the degradation behavior is very complex since it involves the degradation paths of both the polymer matrix and the organomodified nanoclay. In the present work, the effects of mechanical stress and temperature on the thermomechanical behavior of PE-LD/organomodified clay nanocomposites and the degradation paths were investigated by rheological, FT-IR and mechanical methods. The results have shown that the thermomechanical degradation mechanisms are very complex, involving several phenomena such as chain scission, branching, recrystallization and crosslinking, degradation of the organomodified clay and interaction between the degradation products of both system components. These interactions between the degradation products of the organomodifier and the polymer matrix can deeply influence the final behavior of the nanocomposite in a way which is similar to what usually happens in polymer blends.